Destination quality and tourists’ satisfaction: rural tourist destinations in Indonesia - Panduningrum, Tias; Pratminingsih, Astiti; Razak, Anis Abd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to examine the relationship between destination quality towards tourist satisfaction in rural tourist destination. Most study was conducted on established tourist destination and left the rural services behind., The response towards rural destination is getting popular and it is about time that the service provider to get clear informational feedback about their customer expectations. Data were collected from 200 respondent consisted of both local and international tourists. Data was collected with the help of the selected rural destination tourist by requesting their customer to participate upon check out process. All participations were based on voluntary. It took over 2 weeks’ time to gather 212 respondents. Only 200 were usable the rest was incomplete or missing data. The results show that destination quality is important towards tourist satisfaction. It seems that everything related to satisfaction must come along with meeting the expectation and standards set by the tourist. Service provider must carefully look into this area as it may help to grow the business once they managed to fulfil the customer expectations and standards.